Stance Taking in Social Media: the Analysis of the Comments About Us Presidential Candidates on Facebook and Twitter - Kriaučiūnienė, Roma; La Roux, Jefferey; Lauciūtė, Miglė (Verbum, 2018)
[straipsnis ir santrauka anglų kalba]
Keywords: nėra